2011
DOI: 10.1097/nen.0b013e31821ff8d8
|View full text |Cite
|
Sign up to set email alerts
|

Yes-Associated Protein 1 Is Widely Expressed in Human Brain Tumors and Promotes Glioblastoma Growth

Abstract: The hippo pathway and its downstream mediator yes-associated protein 1 (YAP1) regulate mammalian organ size in part through modulating progenitor cell numbers. YAP1 has also been implicated as an oncogene in multiple human cancers. Currently, little is known about the expression of YAP1 either in normal human brain tissue or in central nervous system neoplasms. We used immunohistochemistry to evaluate nuclear YAP1 expression in the fetal and normal adult human brains and in 264 brain tumors. YAP1 was expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
142
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(151 citation statements)
references
References 34 publications
9
142
0
Order By: Relevance
“…48 Matrix metalloproteases (MMPs 7 and 20) have a central role in cell proliferation, migration, differentiation, angiogenesis, apoptosis and host defences and YAP1 is the critical downstream regulatory target in the Hippo signaling pathway, having a pivotal role in organ size control and tumor suppression by restricting proliferation and promoting apoptosis. 49,50 By contrast, the genes contained in the 13q32.1 HZD have not been yet associated with a role in cancer disease. The HZD located at 8p11.23-p11.22 and found in two MGUS patients is also of particular interest, as it contains only the ADAM3A gene, in which HZD has recently been reported in pediatric high-grade glioma and diffuse intrinsic pontine gliomas.…”
Section: %mentioning
confidence: 98%
“…48 Matrix metalloproteases (MMPs 7 and 20) have a central role in cell proliferation, migration, differentiation, angiogenesis, apoptosis and host defences and YAP1 is the critical downstream regulatory target in the Hippo signaling pathway, having a pivotal role in organ size control and tumor suppression by restricting proliferation and promoting apoptosis. 49,50 By contrast, the genes contained in the 13q32.1 HZD have not been yet associated with a role in cancer disease. The HZD located at 8p11.23-p11.22 and found in two MGUS patients is also of particular interest, as it contains only the ADAM3A gene, in which HZD has recently been reported in pediatric high-grade glioma and diffuse intrinsic pontine gliomas.…”
Section: %mentioning
confidence: 98%
“…Overexpression of YAP1 leads to loss of contact inhibition and increases the organ size (Huang et al 2005;Camargo et al 2007). Dysregulation of YAP1 has been identified in various types of cancer (Yuan et al 2008;Liu et al 2010;Wu et al 2010;Orr et al 2011;Zhang et al 2011;Diep et al 2012). Because of its crucial function in tissue growth and tumor development, YAP1 and its regulation have been studied extensively.…”
Section: Discussionmentioning
confidence: 99%
“…YAP is also widely expressed in human brain tumors and esophageal squamous cell carcinoma, and promotes tumor growth. It is indicated that YAP is a putative oncogene and represents a potential diagnostic and therapeutic target (10,11).…”
mentioning
confidence: 99%